Cerebellar Continuous Theta Burst Stimulation for Aphasia Rehabilitation: Study Protocol for a Randomized Controlled Trial - Zheng, Kai; Chen, Mingyun; Shen, Ying; Xu, Xinlei; Gao, Fanglan; Huang, Guilan; Ji, Yingying; Su, Bin; Song, Da; Fang, Hui; Liu, Peng; Ren, Caili (Frontiers in Aging Neuroscience, 2022)
Background Language recovery is limited in moderate to severe post-stroke aphasia patients. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising tool in improving language dysfunctions caused by post-stroke aphasia, but the treatment outcome is as yet mixed. Considerable evidence has demonstrated the essential involvement of the cerebellum in a variety of language functions, suggesting that it may be a potential stimulation target of TMS for the treatment of post-stroke aphasia. Theta burst stimulation (TBS) is a specific pattern of rTMS with shorter stimulation times and better therapeutic effects. The effect of continuous TBS (cTBS) on the cerebellum in patients with aphasia with chronic stroke needs further exploration. Methods In this randomized, sham-controlled clinical trial, patients (n = 40) with chronic post-stroke aphasia received 10 sessions of real cTBS (n = 20) or sham cTBS (n = 20) over the right cerebellar Crus I+ a 30-min speech-language therapy. The Western Aphasia Battery (WAB) serves as the primary measure of the treatment outcome. The secondary outcome measures include the Boston Diagnostic Aphasia Examination, Boston Naming Test and speech acoustic parameters. Resting-state fMRI data were also obtained to examine treatment-induced changes in functional connectivity of the cerebro-cerebellar network. These outcome measures are assessed before, immediately after, and 12 weeks after cerebellar cTBS intervention. Discussion This protocol holds promise that cerebellar cTBS is a potential strategy to improve language functions in chronic post-stroke aphasia. The resting-state fMRI may explore the neural mechanism underlying the aphasia rehabilitation with cerebellar cTBS.